2020
DOI: 10.1177/1464420720980775
|View full text |Cite
|
Sign up to set email alerts
|

Formability prediction of tailor-welded blanks in hydraulic bulging using flow curves from biaxial tensile tests

Abstract: In this work, the formability of laser-welded tailored blanks of low carbon steel of two different thickness combinations in hydraulic bulging has been studied by numerical simulation. For material modeling, flow curves of the parent sheets were obtained in biaxial stress condition by conducting hydraulic bulge tests. These curves were used to extrapolate the uniaxial tensile curves up to large strains using the work equivalence principle. The limiting dome height in conventional forming and hydraulic bulging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…4,5 Despite the mentioned advantages, TWB forming has difficulties such as premature failure, wrinkling, and weld line displacement due to the difference in mechanical properties and nonuniform strain distribution of its constituent sheets. 6,7 Much research has been done to investigate the mechanical properties of TWB. Some studies have shown that by rising the thickness ratio of TWB made of cold-rolled low-carbon steel, 8 the formability decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Despite the mentioned advantages, TWB forming has difficulties such as premature failure, wrinkling, and weld line displacement due to the difference in mechanical properties and nonuniform strain distribution of its constituent sheets. 6,7 Much research has been done to investigate the mechanical properties of TWB. Some studies have shown that by rising the thickness ratio of TWB made of cold-rolled low-carbon steel, 8 the formability decreased.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite the mentioned advantages, TWB forming has difficulties such as premature failure, wrinkling, and weld line displacement due to the difference in mechanical properties and nonuniform strain distribution of its constituent sheets. 6,7…”
Section: Introductionmentioning
confidence: 99%
“…Heo et al [17] investigated how the drawbead dimensions affect the movements of the weld line during the forming of TWBs. Kumar and Digavalli [18] numerically evaluated the formability of low-carbon steel TWBs with two different thicknesses in hydraulic bulging. It was found that with an increase in the thickness ratio, the peak pressure increases, and simulation results will be closer to experimental ones.…”
Section: Introductionmentioning
confidence: 99%